(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
Economists believe that most theories in economics, if not all, can be formulated in terms of minimization or maximization of a suitable economic quantity. Recent studies in geophysics and biophysics have found convincing evidence that the principle driving the origin of life is energy-dissipation-driven adaptation of matter. In this view, life is a result of maximizing entropy production through a maximum dissipation of sunlight energy efficiently transforming it into heat. If this is true, it could be said that in a fundamental sense it is the economic forces that are responsible for the creation of life on earth. To be more accurate, it is the physical forces based on the second law of thermo-dynamics driven by the fundamental economic forces of maximizing entropy along the evolutionary path of the universe that are responsible for the origin of life on Earth. This is not surprising considering the fact that the behaviors of most animal and plant species including their genome itself can be explained in terms of constrained dynamic optimization producing efficient outcomes through decentralized decision making. It is to be recognized that the similarities between the efficient biological system and the efficient economic system, both with efficient decentralized signaling and responses, are more than just coincidental. After all, evidence suggests that the origin of life was a result of economically efficient maximizing of entropy production through a maximum dissipation of sunlight energy driven by the economic forces.